MENINGKATKAN KREATIVITAS BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBASIS MULTIMEDIA - Maryanti Maryanti; Laila Qadriah; Lia Rista (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Ľhe achievement of an education is very dependent on how teaching and learning takes place which requires an increase in the competitiveness of the nation in order to be able to compete in global competition. Where during the pandemic now the learning process is carried out online. Multimedia that is often used by educators is e-learning, zoom, meet, classroom and other applications that use computers / laptops or the like that facilitate the learning process in order to be able to improve students' thinking patterns. Based on the results of observations and interviews conducted at SMA Negeri 1 Lhokseumawe, it shows that students' creativity has problems when the learning process is carried out online. Ľeachers are limited in seeing students' creative abilities because the access used only uses group wa, this is triggered because currently Indonesia is hit by the Covid 19 pandemic which requires teachers to learn online. A person's ability to be successful in navigating his life should be determined by his thinking skills, especially in an effort to solve the life problems he faces. One of the efforts that teachers can do to improve students 'thinking skills is to innovate learning strategies in the learning process that aims to empower students' thinking skills. adapted to the characteristics and environment of students. Ľhe general objective of this study was to determine the extent to which students' creativity through multimedia-based Problem Based Learning (PBL) learning. Ľhis type of research  is  an  experiment.  Ľhis  research  is  an  experimental  study  with  a  pre-test-post-test  control group design. Based on the results of the study, it can be concluded that the increase in the creativity of students who get multimedia-based PBL learning is better than students who receive conventional learning. Ľhis is evident from the resulting value that the N-Gain of mathematical creativity with a value of t = 1.839 and Sig. (2-tailed) = 0.035. Because doing a one-tailed (1-tailed) hypothesis test, the sig. (2-tailed) must be divided into two Sig values. (1-tailed). Because the Sig. (1-tailed) <significance level (α = 0.05), then Ho is rejected